TRAP'd Teens: Impacts of Abortion Provider Regulations on Fertility & Education - Kelly M. Jones; Mayra Pineda-Torres (Institute of Labor Economics (IZA), 2021)
Targeted regulations of abortion providers (TRAP laws) are the fastest growing abortion restriction in the U.S. These often result in clinic closures, limiting abortion access. We study how women's exposure to these laws in adolescence affects their fertility and educational attainment. For this study, we codify the legal history of all TRAP laws ever implemented. We explore the impacts of TRAP laws on teen births using an event-study analysis and stacked differences-in-differences methodology to avoid issues of negative weighting inherent in two-way fixed effects approaches. Consistent with other evidence on abortion access, we find that impacts on births are large and robust for Black women. Black teen births in states that implemented TRAP laws increased by 3 percent relative to changes in states without these restrictions. We offer evidence that these impacts are driven by reductions in abortion access, abortion use, and contraception use among Black teens. We further document that adolescent exposure to TRAP laws has downstream impacts on education. We find that Black women first exposed to TRAP laws before age 18 are 1 to 3 percentage points less likely to initiate and complete college. This study documents the important role that abortion access plays in reducing the harmful economic impacts of unintended teen motherhood. The findings suggest that modern abortion restrictions are harming women's efforts at economic advancement and are perpetuating racial inequality.
Keywords: J13; I24; I14; J15; J16; 330; fertility; education; abortion; adolescence; race